Prognostic value of [18F]FDG PET/CT on treatment response and progression-free survival of gastroesophageal cancer patients undergoing perioperative FLOT chemotherapy. Issue 163 (June 2023) - Mirshahvalad, Seyed Ali; Seyedinia, Seyedeh Sara; Huemer, Florian; Schweighofer-Zwink, Gregor; Koch, Oliver; Hitzl, Wolfgang; Weiss, Lukas; Emannuel, Klaus; Greil, Richard; Pirich, Christian; Beheshti, Mohsen
Highlights: 18 F-FDG PET/CT may help perioperative decision-making in gastroesophageal cancer. 18 F-FDG PET/CT SULpeak might be correlated with pathological response to treatment. 18 F-FDG PET/CT semi-quantitative parameters may predict progression-free survival. Abstract: Purpose: To evaluate the prognostic role of [ 18 F]FDG PET/CT metabolic parameters in gastric cancer (GC) and gastroesophageal adenocarcinoma (GEJAC) patients receiving neoadjuvant chemotherapy. Method: In this retrospective study, 31 patients with biopsy-proven GC or GEJAC were included between August 2016 and March 2020. [ 18 F]FDG PET/CT was performed before the neoadjuvant chemotherapy. Primary tumours' semi-quantitative metabolic parameters were extracted. All patients received a perioperative FLOT regimen thereafter. Post-chemotherapy [ 18 F]FDG PET/CT was performed in most patients (17/31). All patients underwent surgical resection. Histopathology response to treatment and progression-free survival (PFS) were evaluated. Two-sided p-values < 0.05 were considered statistically significant. Results: Thirty-one patients (mean age = 62 ± 8), including 21 GC and 10 GEJAC patients, were evaluated. 20/31(65%) patients were histopathology responders to neoadjuvant chemotherapy, including twelve complete and eight partial responders. During the median follow-up of 42.0 months, nine patients experienced recurrence. The median PFS was 60(95% CI:32.9–87.1) months. Pre-neoadjuvant chemotherapy SULpeak was significantly correlated with pathological response to treatment (p-value = 0.03;odds ratio = 16.75). In survival analysis, SUVmax (p-value = 0.01;hazard ratio[HR] = 1.55), SUVmean (p-value = 0.04;HR = 2.73), SULpeak (p-value < 0.001;HR = 1.91) and SULmean (p-value = 0.04;HR = 4.22) in the post-neoadjuvant chemotherapy pre-operative [ 18 F]FDG PET/CT showed significant correlation with PFS. Additionally, aspects of staging were significantly correlated with PFS (p-value = 0.01;HR = 2.21). Conclusions: Pre-neoadjuvant chemotherapy [ 18 F]FDG PET/CT parameters, especially SULpeak, could predict the pathological response to treatment in GC and GEJAC patients. Additionally, in survival analysis, post-chemotherapy metabolic parameters significantly correlated with PFS. Thus, performing [ 18 F]FDG PET/CT before chemotherapy may help to identify patients at risk for inadequate response to perioperative FLOT and, after chemotherapy, may predict clinical outcomes.